Prevalence and genotype distribution of HPV infection from Hangzhou of Zhejiang Province pre- and during COVID-19 pandemic - Wang, Jian; Zhao, Ke; Xia, Jianping; He, Fang; Chen, Na; Wang, Weijuan; Ma, Yanxiu; Sun, Xiaoming (Frontiers in Public Health, 2024)
Limited data exist on HPV prevalence and genotyping during the COVID-19 pandemic. A total of 130,243 samples from 129, 652 women and 591 men who visited the First People’s Hospital of Linping District between 2016 and 2022 were recruited. HPV genotypes were detected by polymerase chain reaction (PCR) amplification and nucleic acid molecular hybridization. Then the prevalence characteristics of HPV genotypes and trends in HPV infection rates from 2016 to 2022 were analyzed. Results showed that among the study population, the overall prevalence of HPV infection was 15.29%, with 11.25% having single HPV infections and 4.04% having multiple HPV infections, consistent with previous findings. HPV genotypes exhibited similar distribution patterns in both male and female groups, with HPV16, HPV52, HPV58, HPV18, and HPV39 being the most prevalent. Age-related analysis unveiled a bimodal pattern in HPV prevalence, with peaks in infection rates observed in individuals below 20 and those aged 61–65 years. Comparing the pre- and during COVID-19 periods revealed significant disparities in HPV infections, with variations in specific HPV genotypes, including 16, 18, 35, 45, 52, 58, 59, and 68. This study provides valuable insights into the prevalence, distribution, and epidemiological characteristics of HPV infections in a large population. It also highlights the potential impact of the COVID-19 pandemic on HPV trends.